Consumer Decision Making Online shopping In Mataram - Oka Mahardika (Journal of Research in Business, Economics, and Education, 2020)
This study aims to conduct statistical analysis of consumer behaviour making shopping online in Mataram. The data analysis used was statistical analysis in the form of multiple linear regression tests. Sample size is 97 respondent with accidental sampling technique. The data were processed using SPSS 23.0. The results of this study showed that culture factor has no significant effect on consumer decision making online shopping in Mataram, social factor has no significant effect on consumer decision making online shopping in Mataram. personal factor has significant effect on consumer decision making online shopping in Mataram, and psychological has significant effect on consumer decision making online shopping in Mataram. Simultaneously test show that culture, social, personal and psychological factor has significant effect on consumer decision making online shopping in Mataram